Optimalisasi Pengelolaan Surat dalam Mendukung Efisiensi Administrasi Akademik di SMA Al-Hidayah Medan (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
Letter management is one of the important aspects in supporting the efficiency of academic administration in schools. This study aims to explore and understand how letter management at SMA Al-Hidayah Medan can be optimized to improve the efficiency of academic administration. The study used a descriptive qualitative approach with data collection through direct observation and interviews with parties involved in the correspondence administration process. The research findings show that SMA Al-Hidayah Medan implements a combined letter management system, namely combining manual and digital management. Incoming and outgoing letters are recorded manually in the agenda book and expedition book, and archived digitally in the school computer system. However, the system used is still limited and has not been fully integrated. The obstacles found include limited human resources who have not fully mastered administration and information technology, weak document supervision, and archiving of physical letters that have not been systematically arranged. In addition, digital archiving which is still conventional without automatic categorization makes the archive search process less efficient. As an optimization effort, the school has implemented a semi-digital system, provided training for administrative staff, compiled letter classification codes, compiled SOPs for letter management, and utilized cloud storage and digitization of old archives. These steps demonstrate institutional awareness to build a more efficient and modern administration system. In conclusion, effective letter management plays a very important role in supporting academic administration, but requires continuous coaching, better digital integration, and strong managerial commitment.